Lifestyles: propellants factors of obesity in adolescents - Sousa, Filomena (2014)
Although a large collection of results that can identify the causes of obesity is available, it is not an easy task to characterize its etiology. Outstanding among the factors related to overweight and obesity the changes in eating patterns and physical activity, occurred in several societies. About 95% of obesity cases in childhood and adolescence involve exogenous obesity, that is, dependent on environmental factors. Objectives: To analyze lifestyles and eating factors in school adolescents from the town of Bragança. Methods and techniques: Observational, descriptive and cross-sectional study with a sample of 281 school adolescents from the town of Bragança, using a questionnaire. Results: It was found that 63.7% of the young people play sports. Walking is an activity played by 5, 7% of the young people. Most of the teens do few daily meals, have a consumption of products rich in fat (chips) and carbohydrates making meals preferably at home or at the canteen. Family is who, in the opinion of adolescents, more in? uences their diet (59.40%), while the in? uence of health professionals nurses and physicians is not signi? cant. Conclusions: The way as each teenager tealds wih his capital of health a long life wih individual opcions and defined by DGS as lifestyle is a main question on oset of individual and colective health.